Peacebuilding from concept to commission - Jenkins, Rob 1965- (Routledge global institutions series, 2013)
The United Nations Peacebuilding Commission (PBC) was established in December 2005. This book deals with the origins and evolution of peacebuilding as a concept, the creation and functioning of the UN Peacebuilding Commission as an institution, and the complicated relationship between these two processes.